Carbon dioxide mitigation potential of seaweed aquaculture beds (SABs) - Sondak, Calvyn F. A.; Ang, Put O.; Beardall, John; Bellgrove, Alecia; Boo, Sung Min; Gerung, Grevo S.; Hepburn, Christopher D.; Hong, Dang Diem; Hu, Zhengyu; Kawai, Hiroshi; Largo, Danilo; Lee, Jin Ae; et al. (Journal of applied phycology, 2017)
Seaweed aquaculture beds (SABs) that support the production of seaweed and their diverse products, cover extensive coastal areas, especially in the Asian-Pacific region, and provide many ecosystem services such as nutrient removal and CO 2 assimilation. The use of SABs in potential carbon dioxide (CO 2 ) mitigation efforts has been proposed with commercial seaweed production in China, India, Indonesia, Japan, Malaysia, Philippines, Republic of Korea, Thailand, and Vietnam, and is at a nascent stage in Australia and New Zealand. We attempted to consider the total annual potential of SABs to drawdown and fix anthropogenic CO 2 . In the last decade, seaweed production has increased tremendously in the Asian-Pacific region. In 2014, the total annual production of Asian-Pacific SABs surpassed 2.61 × 10 6 t dw. Total carbon accumulated annually was more than 0.78 × 10 6 t y −1 , equivalent to over 2.87 × 10 6 t CO 2 y −1 . By increasing the area available for SABs, biomass production, carbon accumulation, and CO 2 drawdown can be enhanced. The conversion of biomass to biofuel can reduce the use of fossil fuels and provide additional mitigation of CO 2 emissions. Contributions of seaweeds as carbon donors to other ecosystems could be significant in global carbon sequestration. The ongoing development of SABs would not only ensure that Asian-Pacific countries will remain leaders in the global seaweed industry but may also provide an added dimension of helping to mitigate the problem of excessive CO 2 emissions.